A tumor DNA complex aberration index is an independent predictor of survival in breast and ovarian cancer. Issue 1 (8th August 2014) - Vollan, Hans Kristian Moen; Rueda, Oscar M.; Chin, Suet-Feung; Curtis, Christina; Turashvili, Gulisa; Shah, Sohrab; Lingjærde, Ole Christian; Yuan, Yinyin; Ng, Charlotte K.; Dunning, Mark J.; Dicks, Ed; Provenzano, Elena; et al.
Abstract : Complex focal chromosomal rearrangements in cancer genomes, also called "firestorms", can be scored from DNA copy number data. The complex arm‐wise aberration index (CAAI) is a score that captures DNA copy number alterations that appear as focal complex events in tumors, and has potential prognostic value in breast cancer. This study aimed to validate this DNA‐based prognostic index in breast cancer and test for the first time its potential prognostic value in ovarian cancer. Copy number alteration (CNA) data from 1950 breast carcinomas (METABRIC cohort) and 508 high‐grade serous ovarian carcinomas (TCGA dataset) were analyzed. Cases were classified as CAAI positive if at least one complex focal event was scored. Complex alterations were frequently localized on chromosome 8p (n = 159), 17q (n = 176) and 11q (n = 251). CAAI events on 11q were most frequent in estrogen receptor positive (ER+) cases and on 17q in estrogen receptor negative (ER−) cases. We found only a modest correlation between CAAI and the overall rate of genomic instability (GII) and number of breakpoints (r = 0.27 and r = 0.42, p < 0.001). Breast cancer specific survival (BCSS), overall survival (OS) and ovarian cancer progression free survival (PFS) were used as clinical end points in Cox proportional hazard model survival analyses. CAAI positive breast cancers (43%) had higher mortality: hazard ratio (HR) of 1.94 (95%CI, 1.62–2.32) for BCSS, and of 1.49 (95%CI, 1.30–1.71) for OS. Representations of the 70‐gene and the 21‐gene predictors were compared with CAAI in multivariable models and CAAI was independently significant with a Cox adjusted HR of 1.56 (95%CI, 1.23–1.99) for ER+ and 1.55 (95%CI, 1.11–2.18) for ER− disease. None of the expression‐based predictors were prognostic in the ER− subset. We found that a model including CAAI and the two expression‐based prognostic signatures outperformed a model including the 21‐gene and 70‐gene signatures but excluding CAAI. Inclusion of CAAI in the clinical prognostication tool PREDICT significantly improved its performance. CAAI positive ovarian cancers (52%) also had worse prognosis: HRs of 1.3 (95%CI, 1.1–1.7) for PFS and 1.3 (95%CI, 1.1–1.6) for OS. This study validates CAAI as an independent predictor of survival in both ER+ and ER− breast cancer and reveals a significant prognostic value for CAAI in high‐grade serous ovarian cancer. Highlights: The complex arm‐wise aberration index (CAAI) captures focal complex DNA alterations. Compared with other indices of genomic instability, CAAI adds unique information. CAAI is validated as an independent prognostic marker in breast cancer (n = 1950). Prognostic value of CAAI is independent of the 70‐ and 21‐gene classifiers. CAAI is a new independent prognostic marker in ovarian cancer.